Variability of general characteristics of the bottom population and their effectiveness for monitoring the quality of the marine environment - A. V. Moshchenko (Известия ТИНРО, 2023)
There is shown using the two-factor covariation analysis ANCOVA that, from the position of statistics, TPFbio is the only truly suitable index for monitoring and assessment the ecological state of the marine environment, whereas the indices AMBI, M-AMBI and BOPA should be considered as limited suitable and the others as unsuitable. Poor efficiency for the most of biota characteristics has the following three main reasons. Firstly, the number of species in samples from the areas subjected to anthropogenic stress is usually insufficient for correct calculations. Secondly, the influence of seasonal and interannual variability is usually significant and cannot be excluded. Thirdly, accurate taxonomic identification is difficult for juveniles of many species that can lead to unjustified under- or overestimation of many biotic parameters.